Phase Field Modeling of Crack Propagation in Concrete Composite with Imperfect Interface - Le, Gia-Khuyen; Nguyen, Hoang-Quan; Nguyen, Tien-Dung (Engineering, Technology & Applied Science Research, 2024)
In this study, a phase-field model with imperfect interface is developed to simulate the crack behavior of concrete at the mesoscale level. Concrete is treated as a biphasic material, comprising aggregates, a cementitious matrix, and interfaces between them, which are characterized using a level set function. Both cracks and interfaces are represented in a smeared sense by scalar fields ranging from 0 to 1. On the other hand, the displacement jump at the interface is described by an auxiliary field over the entire domain. This model effectively captures the complex crack patterns in concrete, including debonding cracks and bulk cracks. Furthermore, the results show that a strong interface can significantly enhance the mechanical performance of the material.